Local reliability sensitivity method by the reconstructed fraction moment constrained maximum entropy. (November 2022) - Wei, Ning; Lu, Zhenzhou; Hu, Yingshi
Highlights: LS-FP is derived as the weighted sum of two types of failure probability. The strategy of reconstructing the fraction moments is proposed. LS-FP is estimated as a byproduct of reliability analysis in the proposed method. No model evaluations are required. Abstract: The local sensitivity of the failure probability (LS-FP) with respect to the distribution parameter of the random input is very important in the field of structural reliability analysis and the reliability based design optimization (RBDO). It can be used not only to measure the effect of distribution parameters of random inputs on the failure probability, but also to provide the exact gradient for the RBDO. In this paper, the LS-FP with respect to the mean parameters and standard deviation parameters are originally derived as the weighted sum of two types of failure probability, one is the original failure probability and the other one is the integration of reconfigurable probability density function (PDF) in failure domain. By reconstructing the optimal PDF, the maximum entropy method based on the fraction moment constraints is then proposed to estimate the sensitivity of the failure probability, which transforms the LS-FP as a byproduct of the original failure probability estimation and avoids the additional computational cost.